Testing the link between visual suppression and intelligence - Arranz-Paraíso, Sandra (PLoS One, 2018)
The impairment to discriminate the motion direction of a large high contrast stimulus or to detect a stimulus surrounded by another one is called visual suppression and is the result of the normal function of our visual inhibitory mechanisms. Recently, Melnick et al. (2013), using a motion discrimination task, showed that intelligence strongly correlates with visual suppression (r = 0.71). Cook et al. (2016) also showed a strong link between contrast surround suppression and IQ (r = 0.87), this time using a contrast matching task. Our aim is to test this link using two different visual suppression tasks: a motion discrimination task and a contrast detection task. Fifty volunteers took part in the experiments. Using Bayesian staircases, we measured duration thresholds in the motion experiment and contrast thresholds in the spatial experiment. Although we found a much weaker effect, our results from the motion experiment still replicate previous results supporting the link between motion surround suppression and IQ (r = 0.43). However, our results from the spatial experiment do not support the link between contrast surround suppression and IQ (r = -0.09). Methodological differences between this study and previous studies which could explain these discrepancies are discussed.